Use of a twin‐channel endoscope for removal of a lumen‐apposing metal stent that migrated spontaneously after cystogastrostomy. (20th June 2022) - Kobori, Ikuhiro; Katayama, Yasumi; Tamano, Masaya
Abstract : Kobori and colleagues report a case of late‐onset spontaneous internal migration of a lumen‐apposing metal stent in a patient hospitalized with obstructive jaundice caused by a pancreatic fluid collection. Although difficult, it was possible to remove the migrated stent by grasping it with two forceps using a twin‐channel endoscope.